VOLUNTARY TOURISM IN RURAL SPACES IN CURITIBA, PARANÁ, BRAZIL - Hellen Claucia Mendes Pinheiro de Moura Hrycyk; Bruno Martins Augusto Gomes; Letícia Bartoszeck Nitsche (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2020)
The displacement for voluntary work on rural properties is a form of voluntourism in rural areas. Thus, this article aimed to elucidate the main characteristics of voluntourism in rural properties which work with organic agriculture. For that, qualitative research was conducted with organic products farmers who work with voluntourism in the metropolitan region of Curitiba, Paraná, Brazil and quantitative research with volunteers. The results showed that respect to the conduct rules is essential in the rural properties that work with voluntourism. In terms of divulgation, WWOOF (World Wide Opportunities on Organic Farms) is not the only way to act and promote voluntourism in rural areas and respondents identified that there are some flaws in the service offered by this organization. From the surveyed volunteers it was found that the activity attracts mainly young people with university experience. It was concluded that if voluntourism receives more attention from researchers, farmers and public power it has the potential to become an alternative source of income in rural areas and a differentiated tourism product, especially for its intensity in the exchange of knowledge between tourists and rural producers.